Aplikace rozšířené reality v údržbě výrobních strojů - Blaha, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Diplomová práce se zabývá návrhem aplikace rozšířené reality v údržbě obráběcích strojů. Práce obsahuje část rešeršní a část návrhovou. V první části diplomové práce je shrnuta problematika rozšířené reality z obecného hlediska. Součástí je i představení předních výrobců této technologie. Praktická část práce se zabývá návrhem aplikace. Je shrnut myšlenkový proces návrhu od tvorby databáze po výsledný prototyp. Je uvedeno několik možných řešení a z nich je vybráno nejvhodnější. Závěr práce je věnován diskuzi dosažených výsledků a praktickým doporučením.

The master's thesis deals with the design of an augmented reality application for production machine maintenance. The thesis consists of two parts: the theoretical and the design part. The first part of the thesis summarizes the subject matter of augmented reality from a general point of view. It also includes an overview of leading manufacturers. The practical part of the thesis deals with application design. It contains the thought process from the database creation to the final prototype. Several possible solutions are listed, and the most suitable one is selected. The conclusion of the thesis contains a discussion of the results obtained, and practical recommendations for future uses.
Application of augmented reality in maintenance of production machines
Keywords: obráběcí stroje; údržba; rozšířená realita; Unity; Vuforia; production machines; maintenance; augmented reality; Unity; Vuforia